New method for geometrical design of spur gears with asymmetric involute-trochoid profile. - Cárdenas Oliveros, J.; Hernández Ochoa, Daniel; Babilonia Sánchez, G.; Moya Rodríguez, Jorge (Rev. Téc. Fac. Ing. Univ. Zulia)
This paper establishes a general mathematical model of the geometry of asymmetric spur gears with involute - trochoid tooth profile. This method is different of currently used for obtain three-dimensional models of that spur gear kind those, and it can be manipulated by CAD tools, with the geometry and accuracy needed to be used as objects of CAE analysis in subsequent testing.